Production, purification and characterization of an exo-polygalacturonase from Penicillium janthinellum sw09 - MA,YUPING (2016)
ABSTRACT A soil isolate, Penicillium janthinellum sw09 has been found to produce significant amounts of an extracellular pectinase subsequently characterized as exo-polygalacturonase (exo-PG). By optimizing growth conditions, P. janthinellum sw09 produced high amount of exo-PG (16.54 units/mL). The crude enzyme was purified by gel filtration chromatography and two exo-PG activity peaks (designated as PGI and PGII) were revealed. On SDS-PAGE analysis, purified PGII using DEAE-Sepharose FF column, was found to be a single band with a molecular mass of 66.2 kDa. The purified PGII exhibited maximal activity at the temperature of 45 oC and pH 5.0. The stability profiles show that PGII is more stable in the pH range of 4.0-8.0 and below 60 oC. The Km and Vmax for the enzyme was 1.74 mg/mL and 18.08 μmol/ (mL•min), respectively. Due to this enzymatic characterization, this pectinase is an attractive candidate for applications in degradation of pectin.